Subjectivity and argumentation in legal discourse: use of intercalations in civil procedure - Cabral, Tinoco Ana Lúcia (Romanica Olomucensia, 2014)
This study aims at analyzing the use of intercalations in civil procedure texts, by observing its argumentative role as well as its subjective and inter-subjective character. The theoretical framework that supports such analysis is based upon the Argumentative Semantics as well as studies associated with the Linguistic Enunciation theory, on an enunciative and discursive view of the grammar issues. The corpus is made up of three civil procedure texts. The enunciative framework is described as the starting point for the analysis methodology, taking into account the parties involved in the civil procedure, ruled by the adversarial principle. The second step is to analyze the linguistic features used in the texts in order to identify the intention that has determined such choices; intercalations in particular. The analysis results indicate the importance of conducting linguistic studies focused on the language strategy use for the legal practice.
Keywords: argumentation; subjectivity; intercalation; legal discourse; civil procedure.